Improving development strategies in pastoral areas - Headey, Derek D.; Taffesse, Alemayehu Seyoum; You, Liangzhi (International Food Policy Research Institute, 2013)
The recent drought in the Horn of Africa has again generated widespread pessimism about the future of pastoralism in the re-gion. In this paper we argue that a much more balanced development strategy needs to be adopted in pastoralist areas. First, livelihood diversification must become a positive process, through education, infrastructure, and policies facilitating migration and nonfarm investments. Second, economic transformation must involve a social and demographic transition through reduced fertility rates. And third, transformation of the traditional agricultural sector, dominated by livestock, is needed and is inevita-ble for the simple reason that it is simply too large to ignore, and no amount of livelihood diversification can create enough jobs to pull pastoralists out of poverty. Commercialization efforts, drought management practices, and institutional reforms are the three basic pillars to make the sector more profitable and more resilient to droughts. In addition to all this, interventions in pastoralist areas need to make greater use of innovative practices, such as ICTs, mobile service delivery, and spatial clustering of services.